Time to First Cigarette: A Potential Clinical Screening Tool for Nicotine Dependence. Issue 5 (September 2020) - Branstetter, Steven A.; Muscat, Joshua E.; Mercincavage, Melissa
Abstract : Objectives: The time to first cigarette (TTFC) of the day has been identified as the best single-item indicator of nicotine dependence. However, TTFC has not been extensively used in clinical settings and is not a criterion for tobacco use disorder, perhaps due to a lack of information about TTFC's predictive value. This review provides a synthesis of the accumulating literature on TTFC's relationships with nicotine dependence, identify gaps, and inform future clinical and epidemiologic research of potential uses of TTFC. Methods: A systematic review of the literature was conducted using PubMed, Google Scholar, and Web of Science ISI databases. We identified 16 articles examining the relation between TTFC and negative outcomes associated with high levels of nicotine addiction and Tobacco Use Disorders (eg, high levels of nicotine and toxicant exposure, progressive use over time, failed cessation, head-and-neck cancers). Results: Earlier TTFC was consistently associated with greater likelihood of cessation failure and relapse, and higher levels of biomarkers of tobacco exposure. Several of these associations were found among both adult and adolescent smokers, and remained even after accounting for smoking behaviors (eg, cigarettes/day). Conclusions: Earlier TTFC is a key indicator of greater nicotine dependence. Knowledge of a smoker's TTFC may allow clinicians to accurately inform smokers of health risks and assign greater resources during cessation attempts. Smokers may be able to use TTFC to self-select cessation aids and accurately assess their unique smoking-related health risks. TTFC may be a better item than cigarettes/day for accurately quantifying dependence and risk in epidemiologic studies.